Sundatang-Sabah’s lost lute of Borneo - Hamdan, Sinin; Duin, Ezra M.A.; Said, Khairul A.M.; Kipli, Kuryati; Sinin, Aaliyawani E.; Musib, Ahmad F. (North Carolina State University, 2025)
This study determines the note for a sundatang, a traditional musical instrument in Borneo. The sundatang originated from two different ethnics so the strings were tuned differently as well as frets and it clearly produces more than one note. The sound was recorded using a microphone which was connected to a PicoScope and analyzed using Fast Fourier Transform (FFT). The string 1 and 2 for sundatang A are tuned to E4(330Hz) and E3(161Hz) respectively, and sundatang B are tuned to C4#(277Hz) and C3#(138.59Hz) respectively. Open string 1 and the fret from sundatang A was tuned to E4(330), G4#(410), A4#(465), C5#(546), D5(569), and F5(692) where E4-G4#:2Tone, G4#-A4#:1Tone, A4#-C5#:2Tone, C5#-D5:1Tone, D5-F5:2Tone, simplified become 2TT2TT2T. Open string 1 and the fret from sundatang B it was tuned to C4#(277), E4(329), F4(340), F4#(361), G4(389), G4#(425) where C4#-E4:1.5Tone, E4-F4:1Semitone, F4-F4#:1Semitone, F4#-G4:1Semitone, G4-G4#:1Semitone simplified become 1.5TSSSS. The note interval for string 1 and 2 for sundatang A and B can be formulated as y = 67.6x + 332.8 and y = 30.2x + 272.1, respectively. The time frequency analysis of the open strings 1 and 2 displayed a dense distribution of partials while fret 1 to 5 showed a distinct distribution which decrease with fret number.